Prediction of earthquakes: a step towards predicting the unpredictable - Chowdhury, Maheen; Rahaman, Md Abdur; Islam, Tafhim Sadman; Sultana, Rahanuma; Rahman, Anjolika (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.